Evaluation of the Implementation of the Love Curriculum in Shaping Students' Relational Character at State Islamic High Schools: The CIPP Evaluation Model - Farah Muthia; M. Arifky Pratama; Julita Julita; Eza Qurnia Hayati; Suhirman Suhirman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Evaluation of the Love Curriculum Implementation in Shaping Students' Relational Character at State Islamic High Schools: The CIPP Evaluation Model Objective: This study aims to evaluate the implementation of the Love and Compassion Curriculum in shaping students' relational character in Islamic boarding school-based education. Method: This study uses a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews, participatory observation, and document analysis. Results: The Love Curriculum is highly relevant to the objectives of Islamic character education. The implementation of this curriculum is effective in fostering discipline, empathy, and cooperation among students through various coaching activities, such as tahfidzul Qur'an, ta'limul muta'allim, and muhadloroh. Conclusion: The formation of students' relational character is not sufficient through spiritual guidance and internal discipline in Islamic boarding schools alone; it requires continuous social learning that involves schools, families, and communities working collaboratively. Contribution: This study makes a theoretical contribution by emphasizing the relational character as a key indicator of the success of Islamic character education.INDONESIAN: Evaluasi Implementasi Kurikulum Cinta Kasih dalam Pembentukan Karakter Relasional Siswa di SMA: Model Evaluasi CIPPTujuan: Penelitian ini bertujuan untuk mengevaluasi implementasi Kurikulum Cinta Kasih dalam pembentukan karakter relasional siswa pada pendidikan Islam berbasis pesantren. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan model evaluasi CIPP (Context, Input, Process, Product). Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil: Kurikulum Cinta Kasih memiliki relevansi yang tinggi dengan tujuan pendidikan karakter Islam. Implementasi kurikulum ini efektif dalam menumbuhkan kedisiplinan, empati, dan kerja sama antarsantri melalui berbagai kegiatan pembinaan, seperti tahfidzul Qur’an, ta’limul muta’allim, dan muhadloroh. Kesimpulan: Pembentukan karakter relasional siswa tidak cukup hanya melalui pembinaan spiritual dan disiplin internal pesantren, tetapi memerlukan kesinambungan pembelajaran sosial yang melibatkan sekolah, keluarga, dan masyarakat secara kolaboratif. Kontribusi: Studi ini berkontribusi secara teoretis dengan menegaskan karakter relasional sebagai indikator penting keberhasilan pendidikan karakter Islam.Abstract: Evaluation of the Love Curriculum Implementation in Shaping Students' Relational Character at State Islamic High Schools: The CIPP Evaluation Model Objective: This study aims to evaluate the implementation of the Love and Compassion Curriculum in shaping students' relational character in Islamic boarding school-based education. Method: This study uses a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews, participatory observation, and document analysis. Results: The Love Curriculum is highly relevant to the objectives of Islamic character education. The implementation of this curriculum is effective in fostering discipline, empathy, and cooperation among students through various coaching activities, such as tahfidzul Qur'an, ta'limul muta'allim, and muhadloroh. Conclusion: The formation of students' relational character is not sufficient through spiritual guidance and internal discipline in Islamic boarding schools alone; it requires continuous social learning that involves schools, families, and communities working collaboratively. Contribution: This study makes a theoretical contribution by emphasizing the relational character as a key indicator of the success of Islamic character education. Keyword: Evaluation; Love Education Curriculum; Students' Relational Character; CIPP Evaluation Model Abstract: Evaluasi Implementasi Kurikulum Cinta Kasih dalam Pembentukan Karakter Relasional Siswa di SMA: Model Evaluasi CIPP Tujuan: Penelitian ini bertujuan untuk mengevaluasi implementasi Kurikulum Cinta Kasih dalam pembentukan karakter relasional siswa pada pendidikan Islam berbasis pesantren. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan model evaluasi CIPP (Context, Input, Process, Product). Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil: Kurikulum Cinta Kasih memiliki relevansi yang tinggi dengan tujuan pendidikan karakter Islam. Implementasi kurikulum ini efektif dalam menumbuhkan kedisiplinan, empati, dan kerja sama antarsantri melalui berbagai kegiatan pembinaan, seperti tahfidzul Qur’an, ta’limul muta’allim, dan muhadloroh. Kesimpulan: Pembentukan karakter relasional siswa tidak cukup hanya melalui pembinaan spiritual dan disiplin internal pesantren, tetapi memerlukan kesinambungan pembelajaran sosial yang melibatkan sekolah, keluarga, dan masyarakat secara kolaboratif. Kontribusi: Studi ini berkontribusi secara teoretis dengan menegaskan karakter relasional sebagai indikator penting keberhasilan pendidikan karakter Islam.